(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
By introducing new educational standards, the requirements for educational outcomes are changing. The main task of the school today is to train people who can be successful in our world. Primary school is a very important stage in the process of a student’s general education, in four years he needs not only to master the program material of subject disciplines, but also to learn how to study – to become a "professional student".